(untitled) - Dofka, Charline M.; Charline M. Dofka (Clifton Park, NY, 2007)
This book of common dental terms "sound like" pronunciations for over 1,300 terms used in dental practice. Terms are grouped by speciality, and are supported by review exercises, illustrations, and an appendix on word elements. A 60-minute audiotape provides actual pronunciations to help learners master the vocabulary Supplements Text/Audiotape Package 0-7668-8810-X Audiotapes 0-8273-9071-X Instructor's Manual 0-8273-9069-6
Keywords: Dentistry; Dentistry; Dentistry